Optimasi Pemilihan Cluster Head Dengan Bird-Behavior Pada Lingkungan Manet - Desy Intan Permatasari; Waskhito Wibisono (Informatics Engineering Department-UWKS, 2021)
The movement of nodes dynamically in MANET environments (mobile ad-hoc network) is a major challenge today. Selection of the most appropriate method to send a message to the routing layer should be applied to reduce service discovery delay. Service discovery in the mobile ad-hoc network is a network issue that is still studied today, because the mobile ad-hoc environment network there is no central point of administration that set of nodes in the network. To reduce service discovery delay, the cluster mechanism applied to mobile ad-hoc environment network. Nodes are divided into several areas, called clusters, where each cluster has a cluster head in charge of coordinating the movement of the nodes in the cluster. The problem that arises is how to determine the appropriate cluster head. The selection of cluster head which may cause the decrease in the efficiency of network performance. In this study, the authors put forward a proposal for optimizing the cluster head election by adopting the behavior of birds in migrating from one place to another. Parameters that can be used for the selection of cluster head based on the behavior of bird this is the number of neighboring nodes and the amount of energy that is stored on each node. The results showed that the method of election of cluster head by adapting the behavior of ants to service discovery service discovery delay can reduce up to 33.22 ms and improve service success rate of 8.57%.